Kebijakan Moneter dan Implikasinya terhadap Pembangunan Ekonomi dalam Perspektif Islam - Ahmad Mansur (TSAQAFAH, 2013)
The role of government is very important in an Islamic economy. The government is not only responsible for the establishment of Islamic values and norms in the society ,but also in economic matters such as fulfillment of basic needs, achieving full employment, price stability and low inflation, growth and development that lead to economic well being and welfare.  T o achieve that goal, the government certainly needs an appropriate policy to direct the economy into desired goal and direction.One of the policies is monetary policy .Monetary policy refers to the control of the supply of money to achieve and accomplish manageable inflation,price stability ,full employment and steady growth in the economy. This research tries to investigate the role of monetary policy and its implication on economic development in an Islamic perspective conceptually and theoretically. It found that the role of monetary policy is the same as that in modern economy, except that in Islamic economy ,the role of government is to ensure the Islamic values and nor ms to prevail in the society including the establishment of free interest economy and Islamic financial system that is free from interest based. The instruments of monetary policy in an Islamic perspective are not only confined in using open market operation, reserve ratio, discount rate, but also beyond those tools such as credit rationing, lending ratio and profit ratio which are based on the Islamic principles of interest free based economy.